Number one is but number two is not
of more than 1 dot is on an “up and down” line then it’s not a function
Answer:6
Step-by-step explanation:Reorder
2
2
and
−
x
-
x
.
y
=
−
x
+
2
y
=
-
x
+
2
3
x
+
3
y
=
6
3
x
+
3
y
=
6
Replace all occurrences of
y
y
in
3
x
+
3
y
=
6
3
x
+
3
y
=
6
with
−
x
+
2
-
x
+
2
.
y
=
−
x
+
2
y
=
-
x
+
2
3
x
+
3
(
−
x
+
2
)
=
6
3
x
+
3
(
-
x
+
2
)
=
6
Simplify
3
x
+
3
(
−
x
+
2
)
3
x
+
3
(
-
x
+
2
)
.
Tap for more steps...
y
=
−
x
+
2
y
=
-
x
+
2
6
=
6
6
=
6
Since
6
=
6
6
=
6
, the equation will always be true.
y
=
−
x
+
2
y
=
-
x
+
2
Always true
Remove any equations from the system that are always true.
y
=
−
x
+
2
Isolate the variable x.
1-2x=-x-3
1=x-3
x=4
Answer:
The answer is c or x=25
Step-by-step explanation:
The awnser is D but could also maybe be B